Cost-effectiveness of pembrolizumab plus chemotherapy vs. chemotherapy as first-line treatment for advanced biliary tract cancer in China and the US - Luo, Xianmei; Cai, Tingting; Wu, Jinyan; Li, Xingyu; Wang, Xiaofan; Ma, Haiying (Frontiers in Pharmacology, 2024)
Background Pembrolizumab is a potentially valuable treatment. However, patients, doctors, and healthcare decision-makers are uncertain about its cost-effectiveness and an appropriate pricing for this new therapy. This study aims to appraise the cost-effectiveness of pembrolizumab as a first-line treatment for advanced biliary tract cancer (BTC) patients in China and the United States (US). Methods A Markov model was constructed from the perspectives of healthcare systems in both China and the US for pharmacoeconomic evaluation. Patient baseline characteristics and key clinical data were sourced from the KEYNOTE-966 trial (ClinicalTrials.gov, NCT04003636). Costs and utilities were collected from drug cost websites and published literature. Cumulative costs (in USD), life years (LYs), quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs) were measured and compared. Price simulations were conducted under given willingnessto-pay (WTP) thresholds to provide pricing scheme references. The model's robustness was analyzed through one-way sensitivity analysis and probabilistic sensitivity analysis. Results Basic data analysis illustrates that pembrolizumab ($2662.41/100mg) in combination with chemotherapy regimen was not cost-effective relative to chemotherapy regimens at the WTP threshold of $38,201.19 in China, and the additional cost relative to chemotherapy regimens was $77,114.94 (ICER $556,689.47/QALY) while increasing 0.14 QALYs. Pembrolizumab ($54.71/1 mg) also increased efficacy by 0.14 QALYs in the US, but remained also not cost-effective at the US WTP threshold of $229,044, and the total cost increased by $160,425.24 (ICER $1,109,462.92/QALY). Conclusion Compared with chemotherapy, pembrolizumab plus chemotherapy reduces the disease of burden. However, at its current price, it may not be a cost-effective treatment for advanced BTC in both China and the US. This study can aid decision-makers in making optimal choices.